Alaria esculenta, Ulva lactuca, and Palmaria palmata as Potential Functional Food Ingredients for the Management of Metabolic Syndrome - Emer Shannon; Maria Hayes (Foods)
Hypertension, type 2 diabetes (T2D), and obesity raise an individual’s risk of suffering from diseases associated with metabolic syndrome (MS). In humans, enzymes that play a role in the prevention and development of MS include angiotensin converting enzyme (ACE-1) associated with hypertension, α-amylase associated with T2D, and lipase linked to the development of obesity. Seaweeds are a rich source of bioactives consisting of proteins/peptides, polysaccharides, and lipids. This study examined the potential of seaweed-derived bioactives from Alaria esculenta, Ulva lactuca, and Palmaria palmata as inhibitors of ACE-1, α-amylase, and lipase. In vitro enzyme inhibitory assays were used to quantify the bioactivity of the seaweed extracts and compare their half-maximal inhibitory (IC50) values to recognised positive control enzyme inhibitory drugs captopril© (an ACE-1 inhibitor), acarbose (an α-amylase inhibitor), and orlistat (a lipase inhibitor). Three seaweed extracts displayed enzyme inhibitory activities equal to, or more effective than, the reference positive control drugs. These were P. palmata peptides (ACE-1 IC50 94.29 ± 3.07 µg/mL, vs. captopril© 91.83 ± 2.68 µg/mL); A. esculenta polyphenol extract (α-amylase IC50 147.04 ± 9.72 µg/mL vs. acarbose 185.67 ± 12.48 µg/mL, and lipase IC50 106.21 ± 6.53 µg/mL vs. orlistat 139.74 ± 9.33 µg/mL); and U. lactuca polysaccharide extract (α-amylase IC50 168.06 ± 10.53 µg/mL vs. acarbose 185.67 ± 12.48 µg/mL). Proximate analysis also revealed that all three seaweeds were a good source of protein, fibre, and polyunsaturated essential fatty acids (PUFAs). These findings highlight the potential of these seaweeds in the management of diseases associated with MS and as foods.